Mesh-related complications in single-incision transvaginal mesh (TVM) and laparoscopic abdominal sacrocolpopexy (LASC) - Yi-Ling Li; Yu-Wei Chang; Tsai-Hwa Yang; Ling-Ying Wu; Fei-Chi Chuang; Fu-Tsai Kung; Kuan-Hui Huang (Elsevier, 2020)
Objective: Few studies have investigated the long-term impact of synthetic mesh reconstructive surgery for pelvic organ prolapse (POP) on patient outcomes. This study aimed to examine the incidence and risk factors of mesh exposure and the subsequent requirement for surgical interventions due to mesh-related complications. Materials and methods: This retrospective study was conducted from November 2010 to April 2018. We recruited women with Pelvic Organ Prolapse Quantification (POP-Q) stage 3 or 4 who underwent mesh reconstructive surgery for POP, and enrolled 487 women who received transvaginal mesh (TVM) and 110 women who received laparoscopic abdominal sacrocolpopexy (LASC). Assessments included mesh exposure rate and mesh-related complications requiring surgical interventions in both groups. Results: In the LASC group, the overall mesh-related complication rate was 8.18% over a mean follow-up period of 18 months. Concomitant laparoscopic-assisted vaginal hysterectomy was associated with mesh exposure (OR = 9.240; 95% CI = 1.752-48.728). No patients in the concurrent supracervical hysterectomy group were exposed to mesh. In the single-incision TVM group, the overall rate of mesh-related complications was 3.29% over a mean follow-up period of 19 months. Concomitant total vaginal hysterectomy was also a risk factor for mesh exposure (OR = 4.799; 95% CI = 1.313-17.359). Conclusion: Preserving the cervix or uterus decreased the rate of mesh exposure in those undergoing TVM and LASC surgery. The overall rate of mesh-related complications was low after up to 8 years of follow-up. Keywords: Laparoscopic abdominal sacrocolpopexy (LASC), Mesh exposure, Mesh-related complication, Transvaginal mesh (TVM)